Active Bilayer PE/PCL Films for Food Packaging Modified with Zinc Oxide and Casein - Ana Rešček; Ljerka Kratofil Krehula; Zvonimir Katančić; Zlata Hrnjak-Murgić (Croatica Chemica Acta, 2015)
This paper studies the properties of active polymer food packaging bilayer polyethylene/polycaprolactone (PE/PCL) films. Such packaging material consists of primary PE layer coated with thin film of PCL coating modified with active component (zinc oxide or zinc oxide/casein complex) with intention to extend the shelf life of food and to maintain the quality and health safety. The influence of additives as active components on barrier, mechanical, thermal and antimicrobial properties of such materials was studied. The results show that, in comparison to the neat PE and PE/PCL films, some of PE/PCL bilayer films with additives exhibit improved barrier properties i.e. decreased water vapour permeability. Higher thermal stability of modified PE/PCL material is obtained due to a modified mechanism of thermal degradation. The samples with the additive nanoparticles homogeneously dispersed in the polymer matrix showed good mechanical properties. Addition of higher ZnO content contributes to the enhanced antibacterial activity of a material.